Pemanfaatan Media Audio Visual Dalam Meningkatkan Motivasi Belajar Siswa Kelas X SMA Negeri 5 Maros Pada Mata Pelajaran Bahasa Indonesia - Nurul Nurul; Suardi Suardi; Fadilah Herawati (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research is classroom action research which aims to determine the improvement in student learning outcomes in the Indonesian language subject for class X SMA Negeri 5 Maros. The subjects of this research were class X of SMA Negeri 5 Maros for the 2023/2024 academic year with a total of 36 people. This research was carried out in two cycles and each cycle consisted of 6 meetings. The results of this research show that the application of audio-visual based learning media can improve the effectiveness and learning outcomes of students in Indonesian language subjects. Quantitative analysis shows that learning outcomes in the initial test were 38.88%, in cycle I there was an increase of 52.77% and then in cycle II it was 100%. This means that there is a significant increase in student learning outcomes.